2020
DOI: 10.1002/pon.5553
|View full text |Cite
|
Sign up to set email alerts
|

Psychological correlates of physical activity and exercise preferences in metropolitan and nonmetropolitan cancer survivors

Abstract: Objective Interventions to increase physical activity (PA) in cancer survivors have often adopted a “one‐size‐fits‐all” approach and may benefit from being tailored to psychological constructs associated with behavior. The study objective was to investigate the exercise preferences and psychological constructs related to PA among cancer survivors. Methods Posttreatment colorectal, endometrial, and breast cancer survivors (n = 183) living in metropolitan and nonmetropolitan areas completed survey measures of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Such findings contrast with metaanalyses that reveal affective attitudes as a better predictor of behavior in the general population [31,32]. Recent work in cancer survivors also found instrumental attitude, which is closely linked with risk perceptions but not affective attitude predicted PA intention [33]. The perceived health benefits of PA encompassed by instrumental attitudes, similar to risk perceptions, may be more important in intention formation in clinical populations compared to nonclinical counterparts.…”
Section: Discussionmentioning
confidence: 83%
“…Such findings contrast with metaanalyses that reveal affective attitudes as a better predictor of behavior in the general population [31,32]. Recent work in cancer survivors also found instrumental attitude, which is closely linked with risk perceptions but not affective attitude predicted PA intention [33]. The perceived health benefits of PA encompassed by instrumental attitudes, similar to risk perceptions, may be more important in intention formation in clinical populations compared to nonclinical counterparts.…”
Section: Discussionmentioning
confidence: 83%
“…However, contrary to previous ndings [8], a lack of enjoyment did not typify those that did not increase MVPA, nor did enjoyment play a key role in exercise maintenance. Previous research has similarly found that instrumental attitude, but not affective attitude, predicted PA intention in cancer survivors [23,24] while other research supports relations between affective attitudes, and PA participation [25,26].…”
Section: Discussionmentioning
confidence: 93%
“…Remotely delivered interventions using wearables such as PPARCS are attractive because they integrate BCTs that demonstrate promise in the maintenance of PA (e.g., self‐monitoring of behavior and feedback on performance), tend to be of a lower‐intensity (i.e., less contact time), and thus are more scalable. Remotely‐delivered PA interventions using wearables also align with survivor preferences for monitoring/accountability as a source of motivation 8,9 and exercise preferences for walking 10,11 and unsupervised PA 12 …”
Section: Discussionmentioning
confidence: 99%